Influência de tratamentos de superfície e agentes cimentantes na sobrevivência de coroas de Y-TZP recobertas por porcelana - Anami, Lilian Costa [UNESP] (2015)
The aim of this study was to investigate the influence of different treatments of the inner surface of crowns and different luting agents on the survival of crowns made of zirconia partially stabilized by yttrium oxide (YTZP) and porcelain. A first study was performed using finite element analysis, where we compared the values and the distribution of Maximum Principal Stresses (MPS) of flat and anatomical specimens, with variations in the anatomy of ceramic components (crowns composed of Y-TZP and porcelain, with and without contact point, with and without a modified design of Y-TZP supporting the porcelain). The geometries produced in CAD software (Computer-Aided-Design) were imported for a finite element analysis software. A punctual and vertical load of 200 N was carried out on the central node of the models. The MPS distribution was quite similar among the studied models with important stress concentration in the singularity zone. Considering the lack of standardization in the preparation of anatomical specimens for laboratory tests, the choice of the simplified model (flat) could be justified. In a second step, 90 flat preparations were machined in epoxy resin and received crowns with Y-TZP infrastructure made by CAD/CAM system and veneered with porcelain by the stratified technique. Six conditions were tested (n=15): for crowns cemented with Panavia F, four different treatments were evaluated (cleaning with isopropyl alcohol [PC], overglaze application [POG], sandblasting with 125 μm particles of Al2O3 [POA]; sandblasting with 30μm particles of SiO2 [PCJ]); for crowns cemented with glass ionomer cement (CIV) and zinc phosphate (CFZ), the inner surface were cleaned with isopropyl alcohol. The fatigue resistance was evaluated by the number of mechanical cycles required for fracture of the specimens through stepwise loads methodology. Samples were cycled for 5,000 cycles at 200 ...